Understanding the Doping Effect on NiO: Toward High‐Performance Inverted Perovskite Solar Cells - Chen, Wei; Wu, Yinghui; Fan, Jing; Djurišić, Aleksandra B.; Liu, Fangzhou; Tam, Ho Won; Ng, Annie; Surya, Charles; Chan, Wai Kin; Wang, Dong; He, Zhu‐Bing (Advanced energy materials, 2018)
High‐quality hole transport layers are prepared by spin‐coating copper doped nickel oxide (Cu:NiO) nanoparticle inks at room temperature without further processing. In agreement with theoretical calculations predicting that Cu doping results in acceptor energy levels closer to the valence band maximum compared to gap states of nickel vacancies in undoped NiO, an increase in the conductivity in Cu:NiO films compared to NiO is observed. Cu in Cu:NiO can be found in both Cu+ and Cu2+ states, and the substitution of Ni2+ with Cu+ contributes to both increased carrier concentration and carrier mobility. In addition, the films exhibit increased work function, which together with the conductivity increase, enables improved charge transfer and extraction. Furthermore, recombination losses due to lower monomolecular Shockley‐Read‐Hall recombination are reduced. These factors result in an improvement of all photovoltaic performance parameters and consequently an increased efficiency of the inverted planar perovskite solar cells. A power conversion efficiency (PCE) exceeding 20% could be achieved for small‐area devices, while PCE values of 17.41 and 18.07% are obtained for flexible devices and large area (1 cm2) devices on rigid substrates, respectively. Copper‐doped Nickel Oxide (Cu:NiO) nanoparticles are synthesized and applied as hole transport layers in perovskite solar cells. Cu doping results in an increase in carrier concentration, hole mobility and work function of Cu:NiO. Consequently, charge extraction is improved and the losses are decreased. The devices with Cu:NiO have better efficiency than NiO, with a highest PCE exceeding 20%.